Development of Learning Media For The Traditional Indonesian Hairdo Course - Juniastuti, Eni; Tritanti, Asi; Indadihayati, Warda (Green Publisher Indonesia, 2023)
This research aims to explain: 1) the concept of developing instructional media for Traditional Nusantara Hairdo; 2) the process of developing instructional media for Traditional Nusantara Hairdo; 3) the feasibility of instructional media for the Traditional Nusantara Hairdo course. This research is a development study. The video was developed using the Borg and Gall approach, with stages including data collection, video planning, initial product development, product validation by experts, revision based on expert feedback, small-scale field trials, result revisions, large-scale field trials, product revision and improvement, and internal dissemination. Data collection was done using a media feasibility assessment questionnaire. The research subjects included 3 content experts, 2 media experts, and 60 potential users, namely students of the Makeup and Beauty Program, Yogyakarta State University. The research results show that the developed video is an interactive learning video for traditional Nusantara hairdos. The percentage of expert testing results in the learning aspect reached 88.33%, categorized as very feasible; content aspect reached 88.33%, categorized as very easy; and appearance aspect reached 94%, categorized as very feasible. The small-scale trial percentage is interpreted as 88.5% for appearance (very feasible), 91.66% for ease (very easy), and 91.66% for audio (very feasible). The large-scale trial percentage for appearance is 87.9% (very feasible), ease is 86.6% (very easy), and audio is 84.3% (very feasible). Therefore, this interactive learning video is deemed very suitable for use as instructional media for the Traditional Nusantara Hairdo course.